Impact of antibiotic intake on the incidence of extended-spectrum β-lactamase–producing Enterobacterales in sub-Saharan Africa: results from a community-based longitudinal study. (March 2023) - Heinemann, Melina; Kleinjohann, Lukas; Rolling, Thierry; Winter, Doris; Hackbarth, Nina; Ramharter, Michael; Addo, Marylyn; Eibach, Daniel; Phillips, Richard O.; Owusu-Ofori, Alex; Vinnemeier, Christof D.
Abstract: Objectives: The global prevalence of intestinal extended-spectrum β-lactamase–producing Enterobacterales (ESBL-PE) is approximately 17% in communities, with significant variations among regions. This longitudinal study aimed to assess the impact of antibiotic intake on the incidence of intestinal ESBL-PE in Ghanaian pharmacy customers outside of hospitals. Methods: Screening for ESBL-PE was performed in four independent pharmacies in Kumasi, Ghana, using rectal swabs and an ESBL-PE–selective medium. Pharmacy customers purchasing antibiotics were recruited, and those buying non-antibiotic drugs served as controls. Participants who were negative for ESBL-PE provided follow-up swabs for up to 28 days. Results: At baseline, 302 (75%) of 404 participants were colonized with ESBL-PE. Sixty-three participants who were negative for ESBL-PE at baseline received per-protocol follow-up, including 28 individuals who took antibiotics and 35 controls. The cumulative proportions of ESBL-PE in the antibiotics and control groups were 71% (20/28) and 54% (19/35) at the first follow-up (p 0.258), 86% (24/28) and 80% (28/35) at the second follow-up (p 0.741) and 86% (24/28) and 94% (33/35) at the third follow-up (p 0.393), respectively. Discussion: The rate of intestinal ESBL-PE carriage among pharmacy customers outside of hospitals was higher than expected at baseline and further increased during the 28 days of follow-up, irrespective of antibiotic intake. This alarming finding needs to be considered in the antibiotic treatment of outpatients and emphasizes the urgent need for improved prevention strategies, development of new antibiotic drugs and potential future elimination strategies. Further longitudinal studies on ESBL-PE in African communities, also outside of pharmacy settings, are required. Graphical abstract: Image 1